What Drives the B2B Platform Economy? A Qualitative Examination of Current Trends, Success Factors, and the Road Ahead - Inga Stange (Junior Management Science (JUMS), 2022)
Over the past decade, digital platforms have disrupted traditional industries, causing markets to shift and established companies to rethink their business models. While this mainly applied to consumer-oriented sectors so far, it is now assumed that business-to-business (B2B) industries will be the next to join this major transformation wave. From an information system perspective, this study examines which characteristics and modes of operation are responsible for a B2B platform to succeed. By making use of a multiple-case study, drawing on semi-structured interviews with decision-makers from German B2B platform initiatives, and a descriptive report of its current landscape, the paper provides a holistic overview of the multitude of influencing factors on the design of a B2B platform as well as its drivers and barriers. The study contributes to existing literature by consolidating the fragmented state of research and conceptualizing platform considerations into three stages of platform evolution. Its findings suggest that B2B platforms are subject to different mechanisms than their consumer-oriented counterparts and advises platforms to position at the interface of the digital and traditional world by being simultaneously collaborative, simple, scalable, secure, and trusted.
Keywords: 650; Platform economy; B2B platforms; two-sided business models; digital platforms